PENINGKATAN HASIL BELAJAR KPK DENGAN PENDEKATAN CTL DI SD - Johan, Erlinda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study motivated the low student learning outcomes in mathematics teaching material multiple small alliances (KPK). Research purposes to describe the Planning, Execution and Learning Outcomes Improvement Multiples Small Guild (KPK) to Approach Contextual Teaching Learning in Class IV of Padang Alai SDN 03. Methodology in this researched is a classroom action research, the quantitative approach used is qualitative. Observations obtained student learning outcomes in the first cycle of 66, while on the second cycle of student learning outcomes dikperoleh 87.21.   Keywords:  learning outcomes; commission; contextual teaching learning (CTL)